2016
DOI: 10.1111/jai.13119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary L-malic acid supplementation on growth, feed utilization and digestive function of juvenile GIFT tilapiaOreochromis niloticus(Linnaeus, 1758)

Abstract: Summary Two feeding trials (FTs) were conducted in 2013 and 2014, respectively, to determine the optimal L‐malic acid (LMA) level for juvenile GIFT (Genetically Improved Farmed Tilapia) Oreochromis niloticus. Except for the LMA level, the FT1 and FT2 had a similar diet formulation. In FT1, LMA was included at 0 (basal diet), 1, 4, 8, 16 and 32 g kg−1, respectively. After 20 weeks, daily weight gain and feed conversion ratio were improved but not differentiated with 1–8 g kg−1 LMA. Further increasing the LMA su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
(43 reference statements)
2
11
0
Order By: Relevance
“…This can be associated with the length of the feeding period. For instance, it was found that stomach pepsin activity and growth performance significantly increased in tilapia fed diets supplemented with malic acid for a 20‐week period (Chen et al, ). In line with the results, it is evident that pepsinogen activity and/or synthesis in fish were enhanced because of acidified diets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be associated with the length of the feeding period. For instance, it was found that stomach pepsin activity and growth performance significantly increased in tilapia fed diets supplemented with malic acid for a 20‐week period (Chen et al, ). In line with the results, it is evident that pepsinogen activity and/or synthesis in fish were enhanced because of acidified diets.…”
Section: Discussionmentioning
confidence: 99%
“…Organic acids are capable to hinder microbial growth in the feed due to reducing the pH level of the diet and serving as a conserving agent. Furthermore, they can facilitate feed digestion and absorption by chelating various cations and increasing activities of some digestive enzymes for animals (Chen et al, ; Lala, Oso, Okwelum, Ajao, & Adegbenjo, ). Recently, the inclusion of several organic acids or their salts alone or in combination in fish feed has yielded fruitful results on growth performance, feed utilization and disease resistance (Hassaan, Soltan, Jarmołowicz, & Abdo, ; Ng & Koh, ; Ng, Koh, Sudesh, & Siti‐Zahrah, ; Yilmaz, ; Yilmaz, Ergün, & Yıgıt, ; Yilmaz, Sova, & Ergün, ; Yilmaz, ).…”
Section: Introductionmentioning
confidence: 99%
“…For dairy cows, the feed e ciency was improved, the milk yield was increased and the fat content in the milk was subtly changed (12). The growth and feed utilization were found to be improved in tilapia, but an excess supply would compromise the bene cial effect (10). Despite that inconsistent ndings were reported(28), these results showed the potential bene ts of feeding malic acid to animals when applied with suitable nutritional and managerial measures.…”
Section: Discussionmentioning
confidence: 78%
“…Malic acid is a type of dicarboxylic organic acid which showed antimicrobial activity (9). Besides, malic acid is an intermediate in metabolic cycles of organisms for energy production, and could aid digestion and absorption by chelating various cations and enhancing the activities of some digestive enzymes (10). Malic acid has been permitted as GRAS (Generally Recognized As Safe), which does not has adverse effects for human intake or animal feeding when properly used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation